Strategi Perancangan Klausul dalam Kontrak E-Commerce untuk Mencegah Sengketa Daring (Online Dispute) - Adillah, Ishmah Izzati Arianti; Putra, Moh Rafli Awalul; Nugroho, Lucky Dafira (AHKAM, 2025)
This study examines the strategic formulation of clauses in electronic contracts as a preventive effort against the rising number of disputes in e-commerce transactions, with the backdrop of increasing consumer complaints to the Indonesian Ministry of Trade, which reached 20,942 cases as of March 2025—92.7% of which originated from online transactions. The core issue lies in the weak legal protection stemming from unilaterally drafted contracts by business actors, which tend to disadvantage consumers. The objective of this research is to formulate a model of adaptive and equitable digital contract clauses to minimize dispute risks. This study employs a normative legal research method with a conceptual and statutory approach, using primary and secondary legal sources selected through purposive sampling. The findings indicate that the most effective clauses in preventing disputes include provisions on consumer rights and obligations, intellectual property protection, payment terms, product return policies, exoneration clauses, and dispute resolution mechanisms. However, shortcomings persist, such as the unilateral drafting of clauses, lack of transparency, and limited consumer access to justice mechanisms. Therefore, the design of electronic contracts must adhere to the principle of balanced interests between parties, align with the legal requirements of valid agreements under the Indonesian Civil Code (KUHPerdata), the Electronic Information and Transactions Law (UU ITE), and Government Regulation No. 71 of 2019, and incorporate fair, transparent, and accessible dispute resolution systems. The study concludes that an inclusive and proportional digital contract clause model is essential for strengthening consumer legal protection in e-commerce transactions.